(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the prognosis of non neonatal tetanus in children. Study Design: Prospective observational study Place and Duration of Study: This study was conducted at the Department of Pediatrics Medicine, DHQ Teaching Hospital, Dera Ghazi Khan from January 2018 to January 2019. Materials and Methods: A total of 80 children, aged 1-12 years, diagnosed with tetanus, admitted to pediatrics department, were enrolled in this study. Diagnosis was confirmed by clinical evaluation by minimum of 2 independent pediatricians. Courses of illness along with effects of management during hospital stay and on followup visits were recorded in all patients by collecting data from patients or their patents / guardians. Results: Out of a total of 80 children, there were 43 (53.8%) male and 37 (46.2%) female. Mean hospital stay was noted to be 16.3 days with a standard deviation of 3.6 days. Mean incubation period was 6.5 days with a standard deviation of 1.7 days. Mortality was reported in 2 (2.5%) children,while serious complications were observed in 8 (10.0%). Aspiration pneumonia was the commonest complication, found in 6 (7.5%). We noted 60 (75.0%) children to be unvaccinated. Conclusion: Prognosis was better in our setting in comparison to most of the other studies. Case fatality rate was 2.5% while most of the children (75.0%) presentedwith tetanus were unvaccinated.